A comparison of non-financial performance and earnings quality between QIIB and BIB - Yunice Karina Tumewang (Faculty of Economics, Universitas Islam Indonesia, 2019)
This study aims to evaluate and compare the non-financial performance and earnings quality of Islamic Banks in two different counties complying two different accounting standards, namely Qatar International Islamic Bank (QIIB) and Bahrain Islamic Bank (BIB). This study used a quantitative method with secondary data from the annual report of QIIB and BIB. This study sheds light on the financial and non-financial performance of QIIB and BIB as well as the difference between them. It provides a picture for the Islamic Finance industry regarding the performance of these two banks and what the implication of adopting different accounting standard on this case. Additionally, it helps to raise the awareness of society about the existence of Islamic banks and how well they have performed. As far as we are concerned, there is only small number of research on finding the significance of accounting standard adoption toward the performance of Islamic banks, although the urgency is increasingly growing for better convergence and significant development of Islamic banks. This work is an attempt to fill in this gap.